Blebs—Formation, Regulation, Positioning, and Role in Amoeboid Cell Migration - Schick, Jan; Raz, Erez (Frontiers in Cell and Developmental Biology, 2022)
In the context of development, tissue homeostasis, immune surveillance, and pathological conditions such as cancer metastasis and inflammation, migrating amoeboid cells commonly form protrusions called blebs. For these spherical protrusions to inflate, the force for pushing the membrane forward depends on actomyosin contraction rather than active actin assembly. Accordingly, blebs exhibit distinct dynamics and regulation. In this review, we first examine the mechanisms that control the inflation of blebs and bias their formation in the direction of the cell's leading edge and present current views concerning the role blebs play in promoting cell locomotion. While certain motile amoeboid cells exclusively form blebs, others form blebs as well as other protrusion types. We describe factors in the environment and cell-intrinsic activities that determine the proportion of the different forms of protrusions cells produce.